Factors influencing investment decision-making in stock market among millennials in Malaysia - Loke, Kah Huey (2023)
This study investigates the variables influencing Malaysian millennials' stock market investment choices. The research investigation examines the relationship between the dependent variable of stock investment choice and the four independent factors of herding, overconfidence, accounting information, and firm image. In order to better understand how herding, overconfidence, accounting information, and firm image impact stock investing decisions among millennials in Malaysia, the prospect theory is used as the theoretical foundation. The research design employs a quantitative descriptive approach, targeting Malaysian millennial investors who have a CDS account and are currently investing in the Kuala Lumpur Stock Exchange (KLSE). A statistical analysis was performed on the 594 valid responses that have been collected from the survey questionnaire. The results show a significant positive relationship between herding, accounting information, as well as firm image, and stock investing decisions. However, the relationship between overconfidence and stock investment decision is positive but insignificant. The hypothesis of overconfidence is rejected, while those related to herding, accounting information, and firm image are supported by the findings. The study's conclusions imply that for investors to make wise investment decisions in the stock market, they must be aware of the impact that herding, accounting information, and corporate image have on such decisions. The study's theoretical as well as practical implications, limitations, and suggestions for further research are covered in the conclusion.